Another TWIST on Baller-Gerold syndrome - Seto, Marianne L.; Lee, Samson J.; Sze, Raymond W.; Cunningham, Michael L. (American journal of medical genetics, 2001)
Baller‐Gerold syndrome is characterized by craniosynostosis and preaxial upper limb malformations. Wide heterogeneity exists with regard to the presence of additional anomalies. Most of the 31 reported cases involve other malformations, including cardiac, Central Nervous System (CNS), and urogenital anomalies. Baller‐Gerold syndrome is thought to have autosomal recessive inheritance. However, Gripp et al. [1999: Am. J. Med. Genet. 82:170–176] recently provided the first evidence for autosomal dominant inheritance with variable expressivity and severity. A nonsense mutation was found in TWIST, a gene associated with Saethre‐Chotzen syndrome (SCS). Here we report on a male Caucasian patient of nonconsanguineous parents, with synostosis of the coronal, metopic, and sagittal sutures, and bilateral radial ray hypoplasia. The patient's small, round ears with prominent crus helices, and cervical anomalies are common features of SCS. The father had very mild features of SCS. We identify direct paternal transmission of a novel missense TWIST mutation in the highly conserved Helix II domain of this bHLH‐family gene. This report lends further support to the recent findings by Gripp et al. [1999]. Future TWIST mutational analysis on patients with craniosynostosis and radial ray involvement will shed light on whether Baller‐Gerold syndrome should be a distinct entity or some cases should be reclassified as a heterogeneous form of SCS. © 2001 Wiley‐Liss, Inc.